Water defects induced by expansion and electrical fields in DMPCand DMPE monolayers: contribution of hydration and confined water - Almaleck, Samuel Hugo (2012)
The values of capacitance of dimyristoylphosphatidylcholine (DMPC) and dimyristoylphosphatidylethanolamine (DMPE) monolayers on Hg, derived from cyclic voltammetry studies indicate that when the lipids are near the phase transition temperature fractures are formed at a critical area beyond that corresponding to the hydration shell of the lipids in the liquid expanded state. Similar fractures are inferred to be formed when an electric field is applied at constant area, at a breaking potential which is a function of the lipid species. These voltage values denote that energy involved in the transition induced by the electrical field is much higher for DMPE than for DMPC at low areas. This can be explained by the higher intermolecular lateral interactions by H-bonds between the ethanolamine and phosphate groups. However, at larger areas, the energy values for DMPC are as high as for DMPE which is understood to be due to the higher hydration of phosphocholine head groups. This finding gives a new insight in relation to the dynamics of the lipid head groups at the membrane interphase region in terms of the states of water between the lipids. This is congruent with previous results evaluated with the well known ΔΠ vs. surface pressure plots in monolayers of the same lipids at air-water interfaces.